Ekranisasi Novel Keluarga Tak Kasat Mata karya Bonaventura Genta ke Film Keluarga Tak Kasat Mata Sutradara Hedy Suryawan sebagai Materi Pembelajaran Teks Ulasan di SMP - Amalia, Kristia Rizky; Cahyani, Dzikrina Dian; Wijayanti, Asri (Kajian Bahasa dan Sastra (KABASTRA), 2022)
This research was motivated because it did not meet expectations with the emergence of very prominent differences that were far from the reader's imagination before the novel was filmed. The objectives of this study are: (1) To obtain the form that occurs in the ecranization of characters in the novel and film Keluarga Tak Kasat Mata and to produce review text learning materials in junior high school. This study used a qualitative descriptive research design using a comparative descriptive research method. The sources of data in this study are the novel Keluarga Tak Kasat Mata by Bonaventura Genta and the film Keluarga Tak Kasat Mata by Hedy Suryawan. The data of this research are in the form of phrases, sentences, and parts that contain additions, contractions, changes in variations. The data collection used is a read-listen-note technique. The results showed that the most common form of ecranization was the shrinkage aspect. Learning materials developed from the forms of ecranization can be applied to KD 3.11 and 4.11 class VIII SMP regarding review texts.